2012
DOI: 10.1073/pnas.1120437109
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor 1 - insulin-like growth factor binding protein 3 cascade regulates stress-induced senescence

Abstract: Cellular senescence is widely believed to play a key role in tumor suppression, but the molecular pathways that regulate senescence are only incompletely understood. By using a secretome proteomics approach, we identified insulin-like growth factor binding protein 3 (IGFBP3) as a secreted mediator of breast cancer senescence upon chemotherapeutic drug treatment. The senescenceinducing activity of IGFBP3 is inhibited by tissue-type plasminogen activator-mediated proteolysis, which is counteracted by plasminogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 30 publications
6
110
1
Order By: Relevance
“…[25][26][27][28] First, in spns1 hi891/ hi891 fish embryos, our qRT-PCR experiments showed that the expression of glb1 was more than 2-fold enhanced, and serpine1/pai-1 expression, which can also be elevated in cellular and organismal senescence, [29][30][31] became more than 3-fold through 8-fold higher, with the advancing opaque yolk phenotype ( Fig. 6A and B).…”
Section: Concurrent Heritable Defects Of Both Spns1 and Atp6v0ca In Zmentioning
confidence: 86%
“…[25][26][27][28] First, in spns1 hi891/ hi891 fish embryos, our qRT-PCR experiments showed that the expression of glb1 was more than 2-fold enhanced, and serpine1/pai-1 expression, which can also be elevated in cellular and organismal senescence, [29][30][31] became more than 3-fold through 8-fold higher, with the advancing opaque yolk phenotype ( Fig. 6A and B).…”
Section: Concurrent Heritable Defects Of Both Spns1 and Atp6v0ca In Zmentioning
confidence: 86%
“…This probably involves rescue of PAI-1 expression because fibrotic lungs are rich in TGF-␤. Finally, PAI-1 induces replicative senescence in fibroblasts such as MCF-7, IMR-90, and human stromal-derived breast fibroblasts (73)(74)(75). These findings are consistent with ours, showing that PAI-1 is decreased in FL-fibroblasts, which have acquired a highly proliferative/survival phenotype due to hyper-phosphorylation of Akt/PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that the PAI-1-IGFBP-3 cascade promotes stress-induced senescence in human breast fibroblasts (37). Expression levels of IGFBP-3 are increased in response to senescence-inducing stimuli.…”
Section: Pai-1 Deficiency Normalizes Senescence and Telomere Length Inmentioning
confidence: 99%